Exhaled breath analysis in evaluation of psychological stress: A short literature review. (15th May 2018) - Tonacci, Alessandro; Sansone, Francesco; Pala, Anna Paola; Conte, Raffaele
Abstract : Physiological stress is pervasive in today's society. Its detection is normally performed through several unobtrusive methods, driving both caregivers and patients to take measures to reduce the burden of this condition on human health. Among the methods for assessing stress, exhaled breath analysis represents a non‐invasive, real‐time alternative to classic laboratory tests. Therefore, a literature review was performed to assess the presence of altered parameters, related to psychological stress, in exhaled breath. Most studies in our review measured nitric oxide (NO), whose concentration was often correlated, either positively or negatively, with psychological stress, with reasonable scientific support. Other compounds (isoprene, terpene and so on) were rarely studied and with mixed evidence. Further investigations are needed to elucidate the involvement and the pathophysiological role of NO in stress, possibly including a greater number of individuals, as sample size actually represents the main limitation of the work published to date.